Micellar Spectrophotometric Determination of Cobalt in the samples of Alloys and Vitamins with N-(2-thiazolyl)-2-hydroxybenzamide - Khaturia, S.; Chahar, M.; Soni, K.P.; Bhojak, N. (Asian Journal of Chemistry, 2012)
In the present investigation, potential applicability of a novel reagent N-(2-thiazolyl)-2-hydroxybenzamide (NTHB) for the spectrophotometric determination in micellar medium has been reported. The presence of a non-ionic surfactant Triton X-100 has not only enhanced the solubility and stability of the cobalt2+-NTHB complex, but a marked increase in the absorption intensity has been observed. The best results were obtained in the pH range 6-7 and Beer's law is obeyed up to 0.95 ppm with optimum concentration range 0.11-0.85 ppm for the accurate determination of cobalt at λmax 424 nm. Sandell's sensitivity and molar extinction coefficient have been found to be 0.0010 μg/cm2 and 6.3 x 104 mol-1 cm-1 respectively. Effects of time and diverse ions on the absorption intensity have also been studied. The method is selective and successfully been applied to determine cobalt in the samples of alloys and vitamins.